Genetic variability and combining ability for quality parameters in Ethiopian wheat cultivars - Woldegiorgis, Tadesse Dessalegn (University of the Free State, 2003)
Ethiopian cultivars and advanced lines of bread and durum wheat, originally selected for agronomic superiority, were studied for their grain quality parameters under different environments. Direct and indirect measures of quality were used to establish prediction equations of quality to recommend the minimum quality tests to be used in the breeding program of northwestern Ethiopia. • The HMW-GS of bread and durum wheat, the B-LMW and -ˠ-gliadin of durum wheat protein subunit compositions were identified and their associations with quality traits were studied. The combining ability, relative importance of additive and non-additive gene effects, genetic associations and inheritance of grain and quality traits were also investigated. Bread wheat • Genetic variability was detected among genotypes studied in most important quality traits. The loaf volume, which is the final product, ranged between 882.2 to 1010.8 cm3 with protein levels of 10.7-14.3%. The protein content levels of genotypes at the two Ethiopian sites were relatively lower. The mean mixing time increased (up to 5.5 min) with decreasing protein content of genotypes i.e. genotypes grown at the lowest protein site had the longest mixing time. • Among 15 independent grain yield and quality traits studied, flour protein content, SDS-sedimentation test, PIL ratio, gluten content and thousand grain weights explained 73 % of the variation in loaf volume under the higher protein (10-14 %) environment. The variation of mixograph development time due to protein content alone was 37 % at the lower protein environment. • Highly repeatable traits were PIL ratio, break flour yield, SDS-sedimentation volume, hardness index, mixing time and loaf volume ranging from 0.63 to 0.91. Loaf volume had a significant positive correlation with mixograph development time, SDS-sedimentation volume and alveograph gluten strength. • In a combining ability analysis, most studied traits showed significant additive gene effects. The ratio of GCA: SCA was 0.7 to 37. Heritability of mixograph development time (0.81), SDS-sedimentation volume (0.73), hardness index (0.68), grain weight (0.57) and flour yield (0.46) was higher than the rest of the traits. In studied sets of parents, utilizing additive genetic variance would be effective to improve mixing time, SDS-sedimentation volume, flour yield, vitreous kernels and thousand grain weights. • Eleven banding patterns of HMW glutenin subunits i.e., three at Glu-A 1, five at Glu- Bland two at Glu-D 1 were identified in Ethiopian bread wheat genotypes. The frequency of subunits 5+ 10, the high quality scoring alleles, was 78 %. Banding patterns showed significant differences in SDS-sedimentation volume, alveograph gluten strength, and loaf volume. Pattern 1, 7+8, 5+ 10gave the best results in the studied genotypes. Durum wheat The loaf volume ranged from 483-730 cm3 at protein levels of 10.1-12.5 %. Higher loaf volumes could be achieved by selecting for higher SDS-sedimentation volume and protein genotypes. Flour protein content, SDS-sedimentation volume and seed weight explained 69 % of the variation ofmixograph development time. • The frequency of the B-LMW glutenin and )I-gliadin (LMW-2/ ˠ45) subunit combination of proteins with better gluten strength and loaf volume was high in the studied genotypes. The highest bread volume (730 cm3) was recorded by line CD96486 possessing subunit combination of N/7+8 at Glu-AlIBj loci and LMW-2/ ˠ45 at Glu-A3 and Gli-Blloci, respectively.

Ethiopiese cultivars en gevorderde teellyne van brood en durum korings wat oorspronklik geselekteer is vir agronomiese meerderwaardigheid, is vir graan- kwaliteit in verskillende omgewings bestudeer. Direkte en indirekte metings van kwaliteit is gebruik om voorspellende vergelykings van kwaliteit op te stel, om 'n aanbeveling te maak betreffende die minimum kwaliteitstoetse vir gebruik in teelprogramme in die noordweste van Ethiopië. • Die HMG van brood en durum koring, die B-LMG en Y-gliadiene van durum koring proteïen subeenhede samestelling is geïdentifiseer en hul assosiasies met kwaliteitseienskappe is bestudeer. Die kombineervermoë, relatiewe belangrikheid van additiewe en nie-additiewe gene effekte, genetiese assosiasies en oorerflikhede van graan en kwaliteitseienskappe is bestudeer. Broodkoring • Genetiese variabiliteit is gevind tussen genotipes vir meeste van die belangrikste kwaliteitseienskappe. Die broodvolume, wat die finale produk is, varieer tussen 882.2 tot 1010.8 cm3 met proteïenvlakke van 10.7 - 14.3%. Die proteïenvlakke van die genotipes by die twee Ethiopiese lokaliteite was relatief laer. Die gemiddelde mengtyd het toegeneem (tot 5.5 min) met 'n afname in proteïeninhoud van die genotipes bv. genotipes verbou in die lokaliteit met die laagste proteïenvlak, het die langste mengtye. • Van die 15 onafhanklike graan en kwaliteitseienskappe wat bestudeer is, het proteïeninhoud, SDS-sedimentasie toets, P/L verhouding, gluteninhoud en duisendkorrelmassa 73% van die variasie vir broodvolume in die hoë proteïen omgewing verklaar. Die variasie in miksogram ontwikkelingstyd a.g.v. proteïeninhoud alleen, was 37% in die lae proteïen omgewing. Eienskappe met hoë herhaalbaarhede was P/L verhouding, breekmeelopbrengs, SDS-sedimentasie volume, hardheidsindeks, mengtyd en broodvolume. Die herhaalbaarheid varieer tussen 0.63 en 0.91. • Broodvolume het 'n betekenisvolle korrelasie met miksogram ontwikkelingstyd, SDS-sedimentasie volume en alveo-gluten sterkte. • In 'n kombineervermoë ontleding, toon meeste van die bestudeerde eienskappe betekenisvolle additiewe gene effekte. Die verhouding van GCA:SCA het gevarieer tussen 0.7 en 0.37. Oorerflikhede vir mixogram ontwikkelingsytd (0.81), SDSsedimentasie volume (0,73), hardheidsindeks (0.68), graangewig (0.57) en meelblomopbrengs (0.46) was hoër as die res van die eienskappe. In die bestudeerde stelouers, is die benutting van die additiewe genetiese variansie effektief om eienskappe soos mengtyd, SDS-sedimentasie volume, meelblomopbrengs, horingagtige korrels en duisendkorrelmassa te verbeter. o Elfbandpatrone van HMG glutenien subeenhede bv. drie by GIu-AI, vyfby Glu-BI en twee by Glu-D 1 is geïdentifiseer in Ethiopiese broodkoring genotipes. Die frekwensie van subeenhede 5 + 10, die hoë kwaliteitstelling allele, was 78%. Bandpatrone veroorsaak betekenisvolle verskille in SDS-sedimentasie volume, alveograaf glutensterkte en broodvolume. Bandpatrone I, 7+8, 5+10 het die beste resultate gelewer in die bestudeerde genotipes. Dururn koring • Die broodvolume varieer van 483-730 cm3 by proteïenvlakke van 10.1-12.5%. Hoër broodvolumes kan verkry word deur seleksie vir hoër SDS-sedimentasie volume en proteïen genotipes. Meelblom proteïeninhoud, SDS-sedimentasie volume en saadgewig het 69% van die variasie in miksogram ontwikkelingstyd verklaar. • Die frekwensie van die B-LMG gluteniene en V-gliadien (LML-21Y45) subeenhede kombinasie van proteïene met beter gluten sterkte en broodvolume was hoog in die bestudeerde genotipes. Die hoogste broodvolume (730 cm3) is verkry vanaf lyn CD 96486 wat oor die subeenhede kombinasies van N/7+8 by Glu-AI/B 1 loci en LMG- 2/Y-45 by Glu-A3 en Gli-Blloci, respektiewelik.
Thesis (Ph.D. (Plant Sciences (Plant Breeding))--University of the Free State, 2003
Keywords: Wheat -- Genetic aspects; Wheat| -- Breeding -- Ethiopia